2006
DOI: 10.1007/s11517-006-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive continuous estimation of blood flow changes in human patellar bone

Abstract: A photoplethysmographic (PPG) technique to assess blood flow in bone tissue has been developed and tested. The signal detected by the PPG consists of a constant-level (DC) component-which is related to the relative vascularization of the tissue-and a pulsatile (AC) component-which is synchronous with the pumping action of the heart. The PPG probe was applied on the skin over the patella. The probe uses near-infrared (804 nm) and green (560 nm) light sources and the AC component of the PPG signals of the two wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 31 publications
5
78
2
Order By: Relevance
“…It appears from figure 4 thatn remains constant and thus, as hypothesized, blood volume does not change during heart pulsations. This experimentally confirms the hypothesis that in bone there is no significant periodic increase in blood volume due to vasodilation or opening of collaterals (Näslund et al 2006). From this observation it follows that the pulsatile character of can only be determined by the periodic variations in V .…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…It appears from figure 4 thatn remains constant and thus, as hypothesized, blood volume does not change during heart pulsations. This experimentally confirms the hypothesis that in bone there is no significant periodic increase in blood volume due to vasodilation or opening of collaterals (Näslund et al 2006). From this observation it follows that the pulsatile character of can only be determined by the periodic variations in V .…”
Section: Resultssupporting
confidence: 84%
“…It has been found that in human bone pulsations are determined by the changes in V at constantn, which demonstrates the previous hypothesis of Näslund et al (2006). Thus, V pulsations appear to be possibly responsible for μ s (λ) and/or μ a (λ) variations, and consequently for the PPG pulsations.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations